Feminist Ethics against Stigma of Theocracy-Patriarchy: a Reflection of 2014 Presidential Election - Gerung, Rocky (Yayasan Jurnal Perempuan, 2014)
Feminist politics is a perpetual investment in a just civilization. It awares of the injustice structure that is inherently located within the sociological body of patriarchal system. It needs more than voluntary-echo in democracy rather a strong conceptual tools that will enlighten the dialectic transport of communication in democratic system. Any feminists shall be alert to watch and guard, as well as, cynically, radically, monitor the run of the new-elected president—whether he will bring mandate of equality or not. Short-term strategy has been invested to block the new-order regime to take control; and long-term strategy shall be invested to guarantee the system of equality in the new cabinet.